Análise do movimento do saque no tênis de campo por meio de processamento de imagem - diagnóstico visando à melhoria de desempenho - Valim, Bruno (2021)
The present work consists in evaluating the movement of the serve in tennis, through video image processing using the Cinemetria software to render an 3D avatar. The software in C++ programming with specific algorithms for biomechanical analysis of movement, and it proposes to process the data automatically and correlate the kinematics with a specific protocol to measure and quantify key joint points in the human body, perform image acquisition without specific markers in the game scenario itself in such a way that the player can move without interference from special equipment. In addition to image processing, the goal is to identify the mechanical failure and diagnose the movement of the serve with the ball in real game time. The computer visualization structuring the motor gesture through the display of an Avatar rendered in 3D, allows the coach or player to obtain the information and provide a precise diagnosis of the service movement, in addition to analytical feedback for the service training, facilitating correction of the motor gesture, preventing players from training wrongly, and without making an excessive repetitive effort that could impair the service movement, preventing pain and joint injuries. Through the digital signal processing of the serve images, it is possible to obtain specific information by structural temporal modeling of the biomechanics of the serve in tennis, determined through kinematics the technical standards for the variables of the open movement of the serve and to analyze the motor gesture in all segments of levers, planes and anatomical axes of the player.